'It has really amazed me what my body can now do': boundary work and the construction of a body-positive dance community. Issue 5 (27th May 2016) - Hill, Joanne; Sandford, Rachel; Enright, Eimear
Abstract: Boundaries around normative embodiments in physical cultures can be exclusionary if one's embodied identity does not 'fit'. Normative boundaries are particularly marked in codified forms of dance such as ballet. Moves towards body positivity aim to challenge these normative boundaries by redefining what dancers' bodies can look like and how they should move. This paper stems from an appreciative inquiry undertaken with one such project, a gender-neutral, LGBTQ-friendly adult ballet school in the UK; a subcultural context that marks itself as distinct from broader cultures of dance. Interviews with learners are analysed through a Bourdieuian lens to explore the construction and maintenance of a body-positive subculture. Findings suggest that boundaries of ability were crossed, with celebration of all bodies' capabilities, and boundaries of normative gender expression were transformed through a commitment to gender-neutrality and LGBTQ-friendly behaviours. However, boundaries around technical and aesthetic norms, while shifted or challenged, ultimately remained in place.